2018
DOI: 10.1021/acsanm.8b00140
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Antimicrobial Properties of ZnO@ZIF-8 Embedded Silicone against Planktonic and Biofilm Catheter-Associated Pathogens

Abstract: were determined by X-ray diffraction, high resolution electron microscopy, energy dispersive spectroscopy and nitrogen adsorption. The antimicrobial potential of ZnO@ZIF-8 for reduction of microorganisms often implicated with catheter-associated urinary tract infections (CAUTIs) was studied in detail using four target pathogens, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis and Staphylococcus aureus. The ability of the compound to kill all four microorganisms in suspension was established and a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 47 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…The ZnO-ZIF-8 showed a reduction of 6-8 log, when compared to the control solution, over a 24 h period. Finally, authors of this research prepared ZnO-ZIF-8 embedded silicone elastomers with 2 or 4 w/w % and observed that they effectively eliminated all four microorganisms from the surface after 24 h of exposition, showing their utility to prevent CAUTI (Redfern et al, 2018).…”
Section: Use Of Composite Materialsmentioning
confidence: 91%
“…The ZnO-ZIF-8 showed a reduction of 6-8 log, when compared to the control solution, over a 24 h period. Finally, authors of this research prepared ZnO-ZIF-8 embedded silicone elastomers with 2 or 4 w/w % and observed that they effectively eliminated all four microorganisms from the surface after 24 h of exposition, showing their utility to prevent CAUTI (Redfern et al, 2018).…”
Section: Use Of Composite Materialsmentioning
confidence: 91%
“…There are, however, very few studies reporting the formulation of MOFs into polymeric articles for antimicrobial purposes; and those which exist mostly employ metal ion release as the antimicrobial mechanism. [48][49][50][51][52] In this contribution we report the successful formulation of NO-releasing CPO-27 into a model medical polyurethane using solvent casting to generate standalone films. We show that NO gas can be successfully loaded into the composite and released in antibacterial concentrations when in a moist atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Putting the issue of dwell time aside, the release of antibiotic moieties (i.e., rifampicin) have a long history but the increasing threat of bacterial resistance has driven considerable effort to examine alternative antimicrobial agents. Various antimicrobial peptides [100,108,[113][114][115], guanidine derivatives (i.e., poly hexamethyl biguanide, polyarginines) [103,104], quaternary ammonium compounds [96,98], nitric oxide precursors [105,106,116,117], silver [118][119][120] and a host of other small molecules/metal ions or nanoparticles [107,110,118,[121][122][123][124] with possible biocidal activity have all been investigated as potential modifiers for use in catheters and, while these invariably impact bacterial colonisation, they have yet to make the leap to commercial exploitation and/or substantive clinical trials.…”
Section: Biocide Releasementioning
confidence: 99%